Robust dual-channel catalytic degradation relying on organic pollutants via Cu-C composites with directional electron harvest and classical radical species generation - Cao, Mengbo; Gao, Ming; Wei, Xingyue; Zhang, Hanmin (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
[Display omitted] •An electrochemical displacement method enables the ultra-fast synthesis of CuC catalysts.•CuC catalysts exhibit a dual-channel degradation and cycle operation pathway.•The CuC catalysts exhibit high resistance to interference.•The CuC catalysts are sustainable, and offer enhanced efficiency and material stability.•The packed-bed reactor demonstrates practical applicability for large-scale use. Advanced oxidation processes using metal composite catalysts are among the most promising strategies to address the escalating environmental pollution challenges. However, the conversion of metal-activated oxidants into deactivated high-valency metal states remains a significant hurdle in developing catalysts with both high activity and sustained reusability. This study presents an ultra-fast electron tuning preparation strategy, utilizing an energy-efficient and high-yield (72–96%) wet chemical electrochemical displacement method to transform low-performance commercial materials into high-activity Fenton-like nano-catalysts. Due to the framework restructuring, results, supported by XPS, electrochemical tests, density functional theory (DFT), and catalytic kinetics modeling, demonstrate that the synthesized CuC material offers a novel dual-channel catalytic pathway. Unlike traditional metal-based oxidants that generate free radicals through electron loss in a single-channel process (approx. 55%), CuC catalysts introduce a cyclic pollutant degradation mechanism by directly acquiring electrons from the pollutants (approx. 45%). This innovation enables dual-performance degradation of pollutants while promoting the stable operation of the material. The CuC catalyst powder and the constructed packed-bed reactor exhibit remarkable catalytic efficiency in degrading organic pollutants in the presence of various ions, in soil, and across a broad pH range. Additionally, catalytic treatment of water samples demonstrated a significant reduction in toxicity and high reusability, as confirmed by Chlorella and water lily cultivation data. These findings offer valuable insights into the industrial-scale fabrication of next-generation catalysts and the underlying trans-catalytic mechanisms that enhance their environmental applications.